Occupational Health and Safety in the Construction Industry: A Review of Work Practices - Bethell, Helen; Vimonsatit, Vanissorn (Research Publishing Services, 2011)
The high number of fatalities in the construction industry shows the needs for improvement in occupational Health and Safety (OH&S) measures. Civil Engineer, being regarded as a member of 'top tier' management, is prone to have knowledge of OH&S and factors affecting it in the workplace. However, the OH&S training is not always integrated in the tertiary education. The primary intent of this research is to promote OH&S awareness among engineers. In doing so, understanding the nature of the work practices in the construction industry is necessary. This paper reviews the literature on the work practices in the construction industry and compares with the manufacturing industry. The main objective is to highlight the unique work practices within the construction industry that make it vulnerable to poor OH&S outcomes. In this study, the main differences between the two industries, including the use of subcontracting, fatigue management, training and safety culture have been investigated. Based on this study, 40 recommendations have been collated for the improvement of OH&S standard of construction. These recommendations are then analyzed and categorized on the basis of their ease and cost of implementation, as well as their signicance of impact on the OH&S outcomes. The recommendations with extreme priority are presented. It is proposed that these recommendations are incorporated in the safety management system of the principal contractor and subcontractor.